PELAKSANAAN GERAKAN LITERASI SEKOLAH TAHAP PEMBIASAAN DALAM MENUMBUHKAN MINAT MEMBACA MURID - Hasni Rachman; Yulius Mataputun; Robert Masreng; Ewendi W. Mangolo; Albaiti Albaiti; Diki Kurniawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low reading activity index and the high challenge of equalizing organic literacy culture in urban Papua are the background to this research. This problem triggers the importance of optimizing character development to protect students from exposure to urban digital media distractions. The focus of this research is to analyze the implementation of the School Literacy Movement (GLS) in the habituation stage in fostering students' reading interest at SD Negeri Inpres Dok IX, Jayapura City. A qualitative, descriptive method approach was applied, where data were collected through participatory observation techniques, in-depth interviews with eleven key informants, and reinforced by documentation studies. Data analysis was conducted interactively using a cycle of reduction, data presentation, and triangulation-based verification. The research findings indicate that the 15-minute reading activity every morning has been effectively institutionalized as a routine to foster students' mental readiness to learn. The transformation of physical space through optimizing classroom reading corners and corridors as text-rich environments has been proven to provide intensive visual stimulation for the school ecosystem. The main conclusion confirms that strengthening sustainable literacy management based on local Papuan sociocultural wisdom has significantly succeeded in increasing students' self-confidence and expanding their vocabulary mastery. School management is recommended to implement a dynamic book rotation system across classes to prevent lifelong reader boredom. ABSTRAK Rendahnya indeks aktivitas membaca serta tingginya tantangan pemerataan budaya literasi organik di wilayah perkotaan Papua melatarbelakangi penelitian ini. Masalah tersebut memicu pentingnya optimalisasi penumbuhan budi pekerti guna membentengi peserta didik dari paparan distraksi media digital urban. Fokus penelitian ini adalah menganalisis pelaksanaan Gerakan Literasi Sekolah (GLS) tahap pembiasaan dalam menumbuhkan minat membaca murid di SD Negeri Inpres Dok IX Kota Jayapura. Pendekatan kualitatif metode deskriptif diterapkan, di mana data dikumpulkan melalui teknik observasi partisipatif, wawancara mendalam terhadap sebelas informan kunci, serta diperkuat studi dokumentasi. Analisis data dilakukan secara interaktif menggunakan siklus reduksi, penyajian data, dan verifikasi berbasis triangulasi. Temuan riset menunjukkan bahwa aktivitas membaca 15 menit setiap pagi telah terlembaga secara efektif sebagai rutinitas penumbuh kesiapan mental belajar siswa. Transformasi ruang fisik melalui optimalisasi pojok baca kelas dan koridor sebagai lingkungan kaya teks terbukti memberikan stimulasi visual yang intensif bagi ekosistem sekolah. Simpulan utama menegaskan bahwa penguatan manajemen literasi berkelanjutan berbasis kearifan sosiokultural lokal Papua secara signifikan sukses meningkatkan kepercayaan diri dan memperluas penguasaan kosakata murid. Manajemen sekolah direkomendasikan menerapkan sistem rotasi buku yang dinamis lintas kelas guna mencegah kejenuhan pembaca sepanjang hayat.